2011
DOI: 10.1111/j.1537-2995.2011.03248.x
|View full text |Cite
|
Sign up to set email alerts
|

Number of recent sexual partners among blood donors in Brazil: associations with donor demographics, donation characteristics, and infectious disease markers

Abstract: BACKGROUND Brazilian blood centers ask candidate blood donors about the number of sexual partners in the last 12 months. Candidates who report a number over the limit are deferred. We studied the implications of this practice on blood safety. STUDY DESIGN AND METHODS We analyzed demographic characteristics, number of heterosexual partners, and disease marker rates among 689,868 donations from three Brazilian Centers between July 2007 and December 2009. Donors were grouped based on maximum number of partners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
2
17
1
1
Order By: Relevance
“…Currently, Australian donors are not questioned about the number of recent sexual partners. In contrast, in some countries such as Brazil, questions about the number of recent sexual partners are asked during predonation assessment . Considering the merits of including a question assessing the number of recent sexual partners, the study by Goldman and coworkers is relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Australian donors are not questioned about the number of recent sexual partners. In contrast, in some countries such as Brazil, questions about the number of recent sexual partners are asked during predonation assessment . Considering the merits of including a question assessing the number of recent sexual partners, the study by Goldman and coworkers is relevant.…”
Section: Discussionmentioning
confidence: 99%
“…If the new sexual partner does not belong to any risk group as listed in the donor questionnaire, the real impact on donor safety by this subject is disputable indeed. In Norway, it has earlier been reported that the blood donors have “low-risk behaviour” [15], thus contrasting a more recent report from Brazil [16]. It has also been indicated that the combination of a written questionnaire and an oral face-to-face interview does not ensure that the donors provide all relevant information [17].…”
Section: Discussionmentioning
confidence: 99%
“…All these data came from heterogeneous transactional blood donation systems and are now part of our DW, which was built using the practices discussed in this work. Several analytical results were obtained, and can be found in the related references [9, 6, 26, 23, 25, 15]. …”
Section: Discussionmentioning
confidence: 99%